Preparation and improvement electrochemical performance of Ni-Fe doped porous LiMnPO4/C materials - Jilan Li; Zhangbin Liu; Jiarou Ma (Scientific Reports)
Abstract Lithium manganese phosphate (LiMnPO4) is the most promising candidate for the next generation of lithium-ion battery cathode materials due to its 4.1 V(vs. Li/Li+) high voltage platform. At present, the discharge rate performance and cycle stability are still poor. And here, various Fe, Ni co-doped carbon-coated LiMnPO4 composites materials LiMnPO4/C were successfully prepared using coprecipitation and solvothermal methods. Morphological and electrochemical performance analyses were conducted on the LiMnPO4/C materials prepared by different methods to explore the relationship between material morphology and electrochemical performance. Compared with the coprecipitation method, LiMnPO4/C prepared by the solvothermal method has a smaller particle size and a more regular morphology. Moreover, after the addition of glucose as an auxiliary, the particles exhibit a spindle-shaped porous structure, leading to improved cycling performance and rate capability, and demonstrating superior electrochemical properties. At 0.1, 0.2, 0.5, 1, and 2 C, the discharge specific capacities are 121.4, 102.7, 91.2, 81.5, and 53.7 mAh g− 1, respectively. After 100 cycles at 1 C rate, 91% of the initial capacity is still retained. The above results indicate selecting appropriate preparation methods and controlling the structure and morphology of the material, the electrochemical activity of LiMnPO4 can be directly influenced, which providing a new approach to improve the electrochemical performance of LiMnPO4.